Personalized thermal comfort elicitation for human-centric building environments with low-cognitive-load conversational AI - Yizheng Li; Huan Zhao; Guandong Su; Yang Meng; Yongan Zhang; Yan Li; Ruichen Ding; Zhangxing Chen; Jinyue Yan (Building and Environment, 2026)

Dataset of China Kuroshio Extension Observatory (CKEO): Moored Buoy Observations in the Kuroshio–Oyashio Transition Zone - Zhaohui Chen; Yueqi Zhang; Ruichen Zhu; Zhongxiang Fan; Jia-Zhen Wang; Xin Ma; Guoqing Ren; Haiyuan Yang; Lixiao Xu; Xiaopei Lin; Lixin Wu (Advances in Atmospheric Sciences, 2026)
The Kuroshio–Oyashio Transition Zone (KOTZ) serves as a vital dynamic interface between the warm Kuroshio Extension and the cold Oyashio Current. However, severe sea conditions with strong ocean currents, winds and waves pose challenges for sustained in situ observations of both oceanic and atmospheric variables. This paper introduces the China Kuroshio Extension Observatory (CKEO), a moored observatory program designed for long-term observations in the KOTZ. We provide a dataset of meteorological and oceanographic properties, including sea surface wind, air temperature, atmospheric pressure, relative humidity, sea surface temperature, sea surface salinity, ocean currents in the upper 100 m, and temperature profile in the upper 500 m. The CKEO, which began operations in 2019, provides a continuous air–sea observational dataset of the KOTZ to the scientific community and advances the understanding of multiscale physical processes in this region.

Femtosecond laser-fabricated defect-rich PtRe alloy clusters for enhanced alkaline hydrogen evolution - Xianze Zhang; Junwen Xiong; Zhiyi Sun; Ruichen Lu; Zikang Su; Chen Zhang; Qimiao Zhu; Shilong Yuan; Lan Jiang; Shengjie Xia; Liquan Sun; Xingdong Wang; et al. (Chemical Engineering Journal, 2026)

Self-templated fabrication of heterogeneous F doped NiCo-alkoxides/NiCo hydroxides yolk-shelled spheres with enhanced performance for supercapacitors - Xu Zhang; Ying Chen; Shuxian Song; Lu Song; Ruichen Zhai; Yulan Meng; Shaojie Li; Lijuan Wei; Xutong Yang; Anmin Liu (Chemical Engineering Journal, 2025)

Engineering the primary and second coordination sphere of metal-organic framework boosts the peroxidase-like activity - Xin Yuan; Xinghua Chen; Jun Xiong; Yifang Cao; Niya Ta; Ruichen Gao; Shuli Liu; Min-Hua Zong; Xiaoling Wu; Wen-Yong Lou (Chemical Engineering Journal, 2025)

Three-dimensional simulation of wave-induced seabed liquefaction in the Chengdao area - Youqi Wang; Shengyi Jiao; Haibo Chen; Ruichen Cao; Xianqing Lv (Ocean Engineering, 2025)

Identification of active sites for formaldehyde oxidation on mesoporous Pt/CeO2 catalyst at ambient temperature and low humidity - Ruichen Wang; Chao Yu; Juanjuan Gong; Qingfa Su; Hui Chen; Canyan Yang; Shaodi Sun; Zhiwei Huang; Huazhen Shen; Huawang Zhao; Bihong Lv; Xiaomin Wu; et al. (Fuel, 2025)

Oil pollution risks on coastlines in the Eastern China Seas - Ruichen Cao; Junting Guo; Zengrui Rong; Haibo Chen; Xianqing Lv (Environmental Pollution, 2025)

Oil Spill Occurrence and Pollution Risk Assessment Based on Sea State, Oil Platform Location, and Shipping Route Density in the Bohai Sea - Tao Liu; Ruichen Cao; Minxia Zhang; Xing Chen; Fan Bi; Jiangling Xu (Journal of Marine Science and Engineering, 2025)
The Bohai Sea is the only semi-enclosed inland sea in China. With active marine economic activities, it faces a persistently high risk of oil spill accidents. This study assesses the occurrence risk and pollution risk of oil spills by considering factors such as sea state, the location of oil platform, and shipping route density in the Bohai Sea. The results show that the central part of the Bohai Sea, the southern Liaodong Peninsula, and the Bohai Strait area have a relatively high occurrence risk of oil spills due to busy maritime traffic and harsh sea conditions. In contrast, some areas in the northern, western, and southern parts of the Bohai Sea have a relatively low occurrence risk of oil spills because of weak maritime activity intensity and relatively calm sea state. In terms of the oil pollution risk, its distribution in the Bohai Sea shows significant seasonal characteristics, which are mainly comprehensively affected by multiple dynamic factors such as circulation, monsoon, and seawater exchange. Based on the oil pollution risk distribution, seasonally targeted strategies are proposed, which can provide a scientific basis for oil spill prevention and emergency management in the Bohai Sea, and help relevant departments formulate targeted prevention and control strategies.

Interaction and bacterial effects of microplastics pollution on heavy metals in hyporheic sediments of different land-use types in the Beiluo River Basin - Bingjie Li; Zeyu Chen; Yuting Zhang; Ruichen Mao; Jinxi Song; Yongqing Long; Bin Tang; Jiayuan Feng; Myint Myint Nyein (Environmental Pollution, 2025)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

Temporal and spatial variations in squid jigging catch efficiency in the Oyashio Extension region - Zixuan Niu; Zhaohui Chen; Wei Yu; Haihong Guo; Ruichen Zhu; Xiaoyi Zhang (Fisheries Oceanography, 2024)
The abundance of fishery resources significantly impacts the ratio of fishing effort to harvest. However, traditional statistics of fishery catches or commonly used catch per unit effort (CPUE) metrics cannot accurately capture the complexity of resource abundance in the ocean. To address this issue, we propose here a novel approach that integrates the actual fishery catch from vessel logs with fishing duration obtained through automatic identification system (AIS) positioning. This combined analysis eliminates confounding factors and introduces a novel metric called “catch efficiency (CE)” to evaluate fishing operations more accurately, thereby reflecting resource abundance in a more reasonable way. In this study, we focus on the CE of squid in the Oyashio Extension region in the Northwestern Pacific. Our analysis reveals significant temporal and spatial variations of CE, manifesting in both intensity and distribution patterns. Moreover, our findings establish a close relationship between CE and background water mass distribution, chlorophyll‐a concentration, and micronekton biomass. This implies that the resource abundance of squid can be inferred by considering the varying environmental factors within the fishing area.

A multi-target and responsive nanoplatform (MM/ZnS/ATV) combining H2S and atorvastatin for enhanced atherosclerosis therapy - Yinhong Xie; Mengchen Chi; Ruichen Dong; Sui Wu; Jinming Yang; Qin Wang; Junying Chen; Yajun Weng (Chemical Engineering Journal, 2024)

Research on scallop shells transport of the Yantai coastal region in the Bohai Sea - Le Chen; Yibo Zhang; Yongzhi Liu; Ruichen Cao; Xianqing Lv (Frontiers in Marine Science, 2024)
Introduction Bivalve aquaculture is an important pillar of China's fisheries, with over 1 million tonnes of scallop shells produced annually. However, most of these shells are directly discarded into the sea, leading to continuous pollution of the marine and coastal environments, especially the coast of Yantai in the Bohai Sea where a large number of discarded scallop shell have accumulated. Methods To trace the fate of scallop shells in the ocean, this study established a model for the transport of scallop shells, coupling a two-dimensional tidal current model using the adjoint method with a Lagrangian particle model. By simulating nested tidal models, the distribution of tidal residual current in the Yantai coastal region was obtained. Then, a Lagrangian particle model was used to track the transport pathways of pollutants in the sea. Results Driven by the residual current calculated from the tidal model with the actual situation, possible pollutant release areas were inferred. The results of Lagrangian particle tracking experiments indicate that pollutants were released from the upstream accumulation area, specifically the area near Penglai Hulushan, confirming previous speculation. Discussion The scallop shells transport model can accurately simulate the spatiotemporal profile of scallop shells, which is helpful for managing scallop shell resources and improving the level of shell reuse.

The competition of heavy metals between hyporheic sediments and microplastics of driving factors in the Beiluo River Basin - Bingjie Li; Ruichen Mao; Zeyu Chen; Yuting Zhang; Jinxi Song; Nan Li; Bin Tang; Jiayuan Feng; Mingchang Guan (Journal of Hazardous Materials, 2024)

Mechanistic insight into the catalytic CO oxidation and SO2 resistance over Mo-decorated Pt/TiO2 catalyst: The essential role of Mo - Chao Yu; Canyan Yang; Ruichen Wang; Geyu Dai; Hui Chen; Zhiwei Huang; Huawang Zhao; Zuoming Zhou; Xiaomin Wu; Guohua Jing (Chemical Engineering Journal, 2024)

With spatial distribution, risk evaluation of heavy metals and microplastics to emphasize the composite mechanism in hyporheic sediments of Beiluo River - Bingjie Li; Jinxi Song; Mingchang Guan; Zeyu Chen; Bin Tang; Yongqing Long; Ruichen Mao; Jiawei Zhao; Wenjin Xu; Yuting Zhang (Journal of Hazardous Materials, 2024)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Efficient predictor of pressurized water reactor safety parameters by topological information embedded convolutional neural network - Muzhou Hou; Wanjie Lv; Menglin Kong; Ruichen Li; Zhengguang Liu; Dongdong Wang; Jia Wang; Yinghao Chen (Annals of Nuclear Energy, 2023)

Triclocarban exposure aggravates dextran sulfate sodium-induced colitis by deteriorating the gut barrier function and microbial community in mice - Mengyu Qin; Hehua Lei; Yuchen Song; Mengjing Wu; Chuan Chen; Zheng Cao; Cui Zhang; Ruichen Du; Ce Zhang; Xian Wang; Limin Zhang (Food and Chemical Toxicology, 2023)

Exogenous bile acids regulate energy metabolism and improve the health condition of farmed fish - Lei Wang; Gladstone Sagada; Chenyang Wang; Ruichen Liu; Qiang Li; Chen Zhang; Yunzhi Yan (Aquaculture, 2023)

Reconstruction of catastrophic outburst floods of the Diexi ancient landslide-dammed lake in the Upper Minjiang River, Eastern Tibetan Plateau - Junxue Ma; Jian Chen; Zhijiu Cui; Wendy Zhou; Ruichen Chen; Chengbiao Wang (Natural Hazards, 2022)